2017
DOI: 10.3329/kyamcj.v6i2.33746
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan and Diabetes

Abstract: During Ramadan, Muslims fast from dawn to dusk for one lunar month. Although a majority of Muslim patients with type 2 diabetes fast during the month of Ramadan, there are no accepted guidelines for its management during this period. The few studies on this subject suggest that there are important alterations in energy intake and physical activity, and that most patients change their pattern of drug intake. The objectives of this article is to assist in the task of advising diabetic patients who fast and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Journal of Advanced Scientific Research, 2023; 14 (08): Sept.-2023 study were similar when compared to other studies, reported on Lactobacillus species [5,17,20,39]. The probiotic bacteria are generally found capable to ferment different sugars which depends on their enzyme complement.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Journal of Advanced Scientific Research, 2023; 14 (08): Sept.-2023 study were similar when compared to other studies, reported on Lactobacillus species [5,17,20,39]. The probiotic bacteria are generally found capable to ferment different sugars which depends on their enzyme complement.…”
Section: Discussionsupporting
confidence: 84%
“…The inoculated plates were further incubated anaerobically at 37 o C for 24-48 hrs. After incubation, the culture plates were observed for various microbial colonies and number of colonies produced on each plate of different dilutions was recovered [17].…”
Section: Isolation Of Probiotic Bacteriamentioning
confidence: 99%
“…The antibiotic susceptibility of strain is crucial from the safety point of view for their use as potential probiotics because probiotic bacteria may act as potential reservoir of antimicrobial resistance genes and which can be transferred to gastrointestinal tract. Similarly, Hoque et al [22] , tested susceptibility and resistance against various antibiotics. The results showed that, their isolate Lactobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…The inoculated broths were incubated at 37°C for 24 hrs. Then the growth was measured using a spectrophotometer at 620 nm (Hoque et al, 2010).…”
Section: Screening For Probiotic Potential Isolatesmentioning
confidence: 99%
“…Overnight grown culture was inoculated into MRS broth having different bile salt concentrations (0.2%, 0.4%, 0.6%, 0.8% and 1.0%).The inoculated broths were incubated at 37°C for 24 hrs and the growth was measured using a spectrophotometer at 620 nm (Hoque et al, 2010).…”
Section: Bile Salt Tolerance Studymentioning
confidence: 99%